2018
DOI: 10.1186/s12955-018-0990-z
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in persons with dementia using regional dementia care network services in Germany: a one-year follow-up study

Abstract: BackgroundThe majority of individuals with dementia live in the community; thus, regional dementia care networks are becoming increasingly more important for the provision of care. To date, four different types of dementia care networks have been identified in Germany (stakeholder, organisation, hybrid, mission); however, the effect on the quality of life of persons with dementia using such network services has not yet been examined. Moreover, the possible differences in the effect on the quality of life among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…No or only limited associations were observed with pharmacological or non-pharmacological treatments [48,49]. However, a recent German study showed a stable QoL over time in users of dementia care network services at a level slightly above average, indicating no decrease or worsening over time, as could have been expected [50].…”
Section: Alzheimer's and Other Dementiasmentioning
confidence: 86%
“…No or only limited associations were observed with pharmacological or non-pharmacological treatments [48,49]. However, a recent German study showed a stable QoL over time in users of dementia care network services at a level slightly above average, indicating no decrease or worsening over time, as could have been expected [50].…”
Section: Alzheimer's and Other Dementiasmentioning
confidence: 86%
“…There are multiple studies concluding that the physical and emotional ramifications for family members stemming from delivering care to a patient with Alzheimer's disease have an impact on caregiver overload and, subsequently, on the cessation of care‐giving (Abreu, Rodrigues, Sequeira, Pires, & Sanhudo, 2018; Chiao, Wu, & Hsiao, 2015; Ruiz Fernández & Ortega Galán, 2019). Caregiver overload manifests itself as a state of emotional exhaustion, stress and fatigue (Cabote, Bramble, & McCann, 2015; Gräske et al., 2018) and, furthermore, as many other consequences reflected in caregivers feeling dissatisfied with their overall health (Millenaar et al., 2016). Social dysfunction, anxiety and insomnia are prevalent symptoms in family caregivers of patients with dementia of the Alzheimer's type (Ruiz Fernández & Ortega Galán, 2019; Varik, Medar, & Saks, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This appears to be supported by the findings in this study. Whilst this can be seen in QoL studies more broadly, this appears to be more prominent in cases where the same researcher undertakes both assessments [ 11 , 14 ]. Indeed, a paper [ 3 ] highlighted the importance of establishing rapport in quantitative assessments to encourage participants to respond more openly and honestly.…”
Section: Discussionmentioning
confidence: 99%